BB0259 Encompasses a Peptidoglycan Lytic Enzyme Function for Proper Assembly of Periplasmic Flagella in Borrelia burgdorferi - Xu, Hui; Hu, Bo; Flesher, David A.; Liu, Jun; Motaleb, Md A. (Frontiers in Microbiology, 2021)
Assembly of the bacterial flagellar rod, hook, and filament requires penetration through the peptidoglycan (PG) sacculus and outer membrane. In most β- and γ-proteobacteria, the protein FlgJ has two functional domains that enable PG hydrolyzing activity to create pores, facilitating proper assembly of the flagellar rod. However, two distinct proteins performing the same functions as the dual-domain FlgJ are proposed in δ- and ε-proteobacteria as well as spirochetes. The Lyme disease spirochete Borrelia burgdorferi genome possesses a FlgJ and a PG lytic SLT enzyme protein homolog (BB0259). FlgJ in B. burgdorferi is crucial for flagellar hook and filament assembly but not for the proper rod assembly reported in other bacteria. However, BB0259 has never been characterized. Here, we use cryo-electron tomography to visualize periplasmic flagella in different bb0259 mutant strains and provide evidence that the E580 residue of BB0259 is essential for PG-hydrolyzing activity. Without the enzyme activity, the flagellar hook fails to penetrate through the pores in the cell wall to complete assembly of an intact periplasmic flagellum. Given that FlgJ and BB0259 interact with each other, they likely coordinate the penetration through the PG sacculus and assembly of a functional flagellum in B. burgdorferi and other spirochetes. Because of its role, we renamed BB0259 as flagellar-specific lytic transglycosylase or LTaseBb.